Handbook of reconstructive flaps - Hanasono, Matthew M.; Butler, C. E. (Charles E.) (Thieme, 2021)
"Handbook of Reconstructive Flaps by Matthew Hanasono and Charles Butler reflects contributions from clinicians associated with the prestigious MD Anderson Cancer Center. The institution is internationally recognized as one of the world's premier reconstructive centers and renowned for its reconstructive microsurgery fellowship program. This unique resource provides a comprehensive review of microvascular surgery techniques using the most common reconstructive pedicle flaps, free flaps, perforator flaps, and workhorse flaps. Seven parts organized anatomically detail flaps used for the head/neck, chest, back, abdomen, pelvis, upper extremity, and lower extremity, followed by an eighth part on lymphedema. Each flap or procedure includes pertinent anatomy, indications for usage, preoperative considerations, a concise step-by-step description of the operative setup, the actual procedure, and donor site closure. Key Features A pearls and pitfalls section in each chapter outlines key concepts and critical nuances in surgical techniques or patient management More than 200 clear diagrams, line drawings, and illustrative surgical photos enhance the understanding of high impact points High-quality videos posted online elucidate flap techniques A section dedicated to the microsurgical treatment of lymphedema covers lymphovenous bypass and vascularized lymph node transfers This is an essential, user-friendly reference for plastic surgery residents, fellows and plastic surgeons in practice"--